Noninvasive and noncontact sequential imaging of the iridocorneal angle and the cornea of the eye - Hong, Jeesmond Xun Jie (2020)
High-resolution imaging of the critical anatomic structures of the eye, especially of the anterior chamber, in vivo, remains a challenge, even with currently available state-of-the-art medical imaging techniques. This study aims for the noninvasive and noncontact sequential imaging of the iridocorneal angle, especially the trabecular meshwork (TM) and the cornea of the eye in high-resolution using a newly developed imaging platform.